2019
DOI: 10.26675/jabe.v4i1.8524
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Financial Literacy on Financial Behavior

Abstract: A number of previous empirical studies found that, financially speaking, literate people tends to do budgeting, saving, controlling expenses, managing debt well, participating in stock market and planning pension fund, etc. In other words, the higher an individual’s knowledge and understanding of financial concept, the more likely they are to behave financially well in their daily life. Financial literacy is needed by everyone, including womenpreneur because not only they have to be able to manage their person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 19 publications
4
31
0
6
Order By: Relevance
“…According to Mahdzan & Tabiani (2013), financial literacy can be seen in individual financial decision making, starting from making mature financial plans and being able to manage every pattern of financial behavior. This opinion is in line with research conducted by Humaidi et al (2020) and Andarsari & Ningtyas (2019) which revealed that financial literacy affects financial management behavior. The research emphasizes that financial literacy has an important role in shaping one's wealth equity.…”
Section: The Relationship Between Financial Literacy and Financial Ma...supporting
confidence: 90%
See 1 more Smart Citation
“…According to Mahdzan & Tabiani (2013), financial literacy can be seen in individual financial decision making, starting from making mature financial plans and being able to manage every pattern of financial behavior. This opinion is in line with research conducted by Humaidi et al (2020) and Andarsari & Ningtyas (2019) which revealed that financial literacy affects financial management behavior. The research emphasizes that financial literacy has an important role in shaping one's wealth equity.…”
Section: The Relationship Between Financial Literacy and Financial Ma...supporting
confidence: 90%
“…With the various financial activities carried out by the Kupang community, financial literacy is needed to help the community in managing their finances responsibly and not make mistakes in making financial decisions. Based on research conducted by Humaidi et al (2020), Andarsari & Ningtyas (2019) show that financial literacy has an influence on financial management behavior. The research confirms that having a good financial understanding can help individuals make wise financial decisions such as saving more for retirement funds, managing personal finances better, and managing investments carefully.…”
Section: Introductionmentioning
confidence: 99%
“…Financial knowledge has a significant influence on financial behavior. Financial knowledge positively correlates with financial behavior (Andarsari & Ningtyas, 2019;Amagir et al, 2020). Financial education has an essential contribution to financial knowledge and financial behavior to be better [7].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 40% -50% of respondents are most in the criteria of not literate. Not literate respondents are considered to not having an understanding or trust in financial services institutions, financial products and services, also not having skills in using financial products and services [41].…”
Section: Gendermentioning
confidence: 99%